Meta-analysis of the Effect of Interactive Learning Media on Student Learning Outcomes in Islamic Religious Education - Tetambe, Ahmad Ghifari; Marzuki (Dirasah: Jurnal Pendidikan Islam, 2025)
This study aims to systematically examine the effect of interactive learning media on student learning outcomes in Islamic Religious Education (IRE) through a meta-analysis approach. This study is based on the phenomenon of low effectiveness of IRE learning, which still largely uses conventional approaches and is not responsive to the characteristics of the digital generation. Meta-analysis was used to integrate data from 10 quasi-experimental studies that met the inclusion criteria, with a publication range from 2019 to 2025. The results showed that all studies produced a large effect size, with a combined correlation coefficient value of 0.7365. These findings indicate that interactive media such as Canva, Kahoot, Mentimeter, Wordwall, as well as audiovisual media and animation have a significant influence on student learning outcomes in Islamic Religious Education, both cognitively and affectively. Theoretically, these results are supported by the Cognitive Theory of Multimedia Learning and the social constructivism approach, which explain that learning is more effective when it involves multimodal interaction and active participation. This research provides theoretical and practical contributions to the development of a more adaptive, contextual, and technology-based religious education model, and can be used as a reference by teachers, curriculum developers, and policy makers in designing PAI learning strategies that are relevant to the challenges of the 21st century.